VIRTUAL CFRP STRENGTHENING OF NON-PRISMATIC RC BEAMS WITHOUT LATERAL REINFORCEMENT - Ali Hameed Aziz (Journal of Engineering and Sustainable Development, 2022)
The provision of the international codes does not cover clearly the design of non-prismatic reinforced concrete beams and the design has been left to the experience and judgment of design engineers. In the present paper, four beam specimens were cast and tested, one of which was poured as a prismatic beam (reference beam), while, the others were poured with non-prismatic sections. Virtual strengthening with bonded CFRP strips was adopted as an alternative technique instead of the real lateral reinforcement (stirrups) to evaluate the degree at which the load-carrying capacity of tested beam specimens was enhanced. Finite element method, as a numerical solution by ANSYS software, was adopted to simulate all the tested beam specimens which presented as three-dimensional problems. Experimental results show that the degradation due to tapering was varied between (50-94%) and (53-81%) for the ultimate and cracking load respectively, in comparison with the reference beam. While the analysis results indicated that the adopted technique plays important parameters to enhance the performance of the strengthened beams and the presence of CFRP increased the strength in the case of stirrups-less beams.